Effect of cryoprotectants on the cryopreservation of Oncidium baueri lindl. Pollinia in liquid nitrogen - Suzuki, Ana Beatryz Prenzier; Sorace, Mauren; Pedro Junior, Sérgio; Tejo, Débora Perdigão; Barata, Gabriel Cruz; Biz, Guilherme; Faria, Ricardo Tadeu de (Ornamental Horticulture, 2025)
The genus Oncidium Sw., one of the largest in the Orchidaceae family, comprises 315 species, 94 of which are native to Brazil. The trade of native orchids through extractivism, combined with habitat destruction, poses a significant threat to biodiversity and has led to the extinction of several species. Cryotechnology has emerged as a crucial tool in the conservation of plant genetic resources, particularly through cryopreservation. This study aimed to evaluate the effects of different cryoprotectant solutions on the viability of Oncidium baueri Lindley pollinia after cryopreservation in liquid nitrogen. Two control groups and seven treatments were tested: C1 – freshly collected pollinia used immediately for pollination; C2 – pollinia cryopreserved without cryoprotectants; T1 – 2 M glycerol; T2 – 2 M glycerol + 0.4 M sucrose; T3 – 0.4 M sucrose; T4 – PVS1; T5 – PVS2; T6 – PVS2 + 1% phloroglucinol; and T7 – PVS3. The experimental design was completely randomized, with 10 repetitions of 10 pollinated flowers per treatment. Pollinia used immediately (C1) achieved 83% capsule formation. PVS2 (T5) demonstrated the highest recovery rate (82%), significantly outperforming C2, T1, T4, T6, and T7, which formed capsules at rates of 11%, 3%, 63%, 62%, and 63%, respectively. Pollinia in T2 and T3 did not survive. These findings suggest that PVS2 is the most effective cryoprotectant for the conservation of O. baueri pollinia, contributing to improved strategies for orchid preservation.